Be nice to Marilyn - Luttrell, Ida.; Johnson, L. S. (Lonni Sue) (New York : Atheneum ; Toronto : Maxwell Macmillan Canada ; New York : Maxwell Macmillan International, 1992)
Penny tries to be nice to her visiting cousin Marilyn, but all Marilyn wants to do is create confusion and destruction on the farm.
Keywords: Cousins -- Fiction; Farm life -- Fiction